2009
DOI: 10.1007/s00221-009-2026-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of haptic guidance, aging, and initial skill level on motor learning of a steering task

Abstract: In a previous study, we found that haptic guidance from a robotic steering wheel can improve short-term learning of steering of a simulated vehicle, in contrast to several studies of other tasks that had found that the guidance either impairs or does not aid motor learning. In this study, we examined whether haptic guidance-as-needed can improve long-term retention (across 1 week) of the steering task, with age and initial skill level as independent variables. Training with guidance-as-needed allowed all parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 39 publications
12
101
0
Order By: Relevance
“…In accordance with previous research, driving with continuous guidance and bandwidth guidance was found to improve drivers' lane-keeping performance compared to manual driving (Flemisch et al, 2008;Kienle, Dambock, Bubb, & Bengler, 2012;Marchal-Crespo, McHughen, Cramer, & Reinkensmeyer, 2010;Petermeijer et al 2015a). The Band condition yielded improved TOR compared to Manual but did not improve the absolute lateral error.…”
Section: Effectiveness Of the Band Systemsupporting
confidence: 90%
“…In accordance with previous research, driving with continuous guidance and bandwidth guidance was found to improve drivers' lane-keeping performance compared to manual driving (Flemisch et al, 2008;Kienle, Dambock, Bubb, & Bengler, 2012;Marchal-Crespo, McHughen, Cramer, & Reinkensmeyer, 2010;Petermeijer et al 2015a). The Band condition yielded improved TOR compared to Manual but did not improve the absolute lateral error.…”
Section: Effectiveness Of the Band Systemsupporting
confidence: 90%
“…In line with this observation, Crespo et al [60] found that in learning to steer a simulated vehicle, haptic "guidance-as-needed" was more effective than "fixed guidance". Augmented feedback may benefit learning complex motor tasks (timing, balancing, complex sports movements) [61]- [63] and may assist beginners to prevent mental overload [61].…”
Section: How To Support the Drivermentioning
confidence: 84%
“…Marchal-Crespo et al conducted an experiment in [11] where participants had to drive in a driving simulator, with forces applied by steering wheel to their hands when errors were made. The aim of these forces were to correct the steering wheel motion and to put the users back on the right way.…”
Section: Error Orientation Feedbackmentioning
confidence: 99%